The Relevance of Islamic Boarding School Curriculum to Religious Moderation Based on the Decree of the Director General of Islamic Education No. 7272 of 2019 and Its Impact on the Religious Life of the Community: A Case Study in Cirebon Regency - Makmun, Syukron (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This study analyzes the relevance of pesantren curriculum to religious moderation values within the context of Indonesian national policy, specifically the Directorate General of Islamic Education Decree No. 7272 of 2019. Using a qualitative approach with case study methods in Cirebon Regency, this research explores how variations in pesantren curricula can produce consistent religious moderation values through kitab kuning instruction and pesantren culture. Data were collected through in-depth interviews with 25 informants (kiai, santri, alumni, and community leaders), participatory observation over 8 months, and curriculum documentation analysis from 4 different pesantren. Findings indicate that despite variations in curriculum structure across pesantren, the use of similar kitab kuning and internalization of pesantren values produce graduates with consistent moderate orientations. Religious moderation principles such as tawasuth, i'tidal, tasamuh, and musyawarah are integrated into sorogan and bandongan learning methods. Pesantren alumni prove to play strategic roles in maintaining social cohesion and countering radicalism in society. This research contributes to academic discourse on the role of traditional Islamic education in shaping religious moderation in the contemporary era.